Effectiveness of soybean extract on breast milk production adequacy among postpartum mothers - Fharamita; Ningrum, Novalia Widiya; Hasanah, Siti Noor; Friscila, Ika (Health Sciences International Journal, 2026)
Background: Exclusive breastfeeding remains a global public health priority, yet its coverage in Indonesia has declined in recent years. In Central Kalimantan, the prevalence of exclusive breastfeeding was only 55.78% in 2023, with some districts reporting even lower rates. One of the major barriers is inadequate breast milk production, which is often influenced by maternal physiology, psychological well-being, and nutritional status. Soybean extract, rich in isoflavones, proteins, and bioactive compounds, has been suggested as a natural galactagogue that stimulates prolactin and oxytocin release, thereby enhancing lactation. Objective: This study aimed to evaluate the effectiveness of soybean extract in improving breast milk adequacy among postpartum mothers. Method:  A pre-experimental one-group pretest–posttest design was applied, involving 15 postpartum mothers (7–14 days after delivery) recruited through purposive sampling in the working area of Tumbang Talaken Health Center, Central Kalimantan. Participants consumed 220 ml of standardized soybean extract twice daily for seven consecutive days. Breast milk adequacy was assessed using a structured dichotomous questionnaire covering maternal (breast engorgement, milk leakage) and infant indicators (urination frequency, weight gain, sleep duration). Data were analyzed using McNemar’s test, with a significance level of p < 0.05. Result: Prior to the intervention, only 4 mothers (26.7%) reported adequate milk production, while 11 (73.3%) experienced insufficiency. After seven days of soybean extract consumption, 13 mothers (86.7%) achieved adequate production, and only 2 (13.3%) remained insufficient. McNemar’s test confirmed a statistically significant improvement (p = 0.004). Conclusion: Soybean extract significantly improved breast milk adequacy among postpartum mothers. As an affordable, accessible, and culturally acceptable intervention, soybean extract shows promise as a nutritional strategy to address lactation challenges and support national goals for improving exclusive breastfeeding coverage.